Test-retest reliability of an Android application (Protractor) for range of motion evaluation - Sabah Mohamed Elkady; Reda Kotb Abd Elrazik; Hossam Mohammed Alsaid; Mohammed Youssef Elhamrawy; Ahmed Mashaal; Amany Refaat Mohamed Abdel Wahid; Doaa Atef (Universidad de Murcia, 2023)
Article accepted. The article will be published here soon. Pending final quality checks.